2011
DOI: 10.4028/www.scientific.net/amr.186.126
|View full text |Cite
|
Sign up to set email alerts
|

Study of Fluorescence Spectrum for Measurement of Soluble Solids Content in Navel Orange

Abstract: On-line nondestructive estimation of fruit internal quality greatly benefits the consumer and the fruit industry as a whole because it can ensure the safety and processed product consistency. This research was aimed to build prediction model of soluble solids content (SSC) in navel oranges using ultraviolet lamp induced fluorescence technique. Total 254 navel oranges were separated into the calibration set (170 samples) and prediction set (84 samples). The actual SSC of navel oranges were measured using a digi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Previous studies had shown that UV light at certain wavelengths could produce fluorescence emissions which contain information about the physicochemical changes of the fruit. Li et al (2011) reported that the excitation of UV light onto navel orange fruit at a wavelength of 365 nm was able to produce emissions identified at wavelengths 385-414 nm. Fluorescence spectroscopy could be developed for non-destructive measurement of the fruit maturity index of satsuma mandarin (Citrus unshiu Marc) (Muharfiza et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had shown that UV light at certain wavelengths could produce fluorescence emissions which contain information about the physicochemical changes of the fruit. Li et al (2011) reported that the excitation of UV light onto navel orange fruit at a wavelength of 365 nm was able to produce emissions identified at wavelengths 385-414 nm. Fluorescence spectroscopy could be developed for non-destructive measurement of the fruit maturity index of satsuma mandarin (Citrus unshiu Marc) (Muharfiza et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the rapid development of sensors, non-destructive detection technology has been used in fruit quality evaluation. For example, multispectral [ 4 , 5 ], fluorophore [ 6 , 7 , 8 ], near-infrared spectroscopy [ 9 , 10 , 11 , 12 ], electronic nose [ 13 , 14 , 15 ], and dielectric technology [ 16 , 17 ] have been applied for the evaluation of the soluble solid content in fresh fruits. Among these technologies, near-infrared spectroscopy is currently the most widely used method for evaluating fresh fruit SSC due to its fast, simple, and non-destructive characteristics.…”
Section: Introductionmentioning
confidence: 99%